Analysis of Teachers' Personality Competence in the Manuscript "Sedikit Tentang Pendidikan" by Haji Ismail Arsyad - Apjan, Syarifah Sajila; Mahrus, Erwin (AT-TURATS, 2024)
This study aims to analyze the teacher personality competencies outlined in the manuscript Sedikit Tentang Pendidikan by Haji Ismail Arsyad. The continuing prevalence of moral decay in educational settings serves as the rationale for investigating the teacher personality competencies presented in this manuscript, as they offer significant relevance for application in educational contexts.The research employs a descriptive-analytical method with a qualitative approach, utilizing content analysis for data collection. The primary data source was the manuscript transcribed by Dr. Erwin Mahrus, S.Ag., complemented by secondary sources such as related books and journals. The findings reveal that the manuscript Sedikit Tentang Pendidikan emphasizes several key personality traits that teachers should possess, including a strong character, authority, noble morals, and the ability to serve as role models for students. This study is expected to contribute to the development of teacher personality competencies in the field of education and offer valuable insights for academics, educators, and society at large.Tujuan dari penelitian ini untuk menganalisis kompetensi kepribadian guru yang ada di dalam manuskrip karya Haji Ismail Arsyad yang berjudul “Sedikit Tentang Pendidikan.” Masih menjamurnya dekadensi moral di bangku pendidikan menjadi alasan kenapa kompetensi kepribadian guru dalam manuskrip ini perlu dikaji. Sebab di dalam manuskrip ini terkandung kompetensi kepribadian guru yang sangat relevan diterapkan di bangku pendidikan. Metode yang digunakan dalam penelitian ini ialah metode deskriptif analitik dengan pendekatan kualitatif serta pengumpulan data menggunakan teknik content analysis. Sumber primer dalam penelitian ini ialah manuskrip karya Haji Ismail Arsyad yang telah dialih aksarakan oleh Dr. Erwin Mahrus, S.Ag. Sementara sumber sekunder yang peneliti gunakan yaitu buku dan jurnal-jurnal yang berkaitan. Hasil penelitian ini menunjukkan bahwa di dalam manuskrip “Sedikit Tentang Pendidikan” ada beberapa kepribadian khas yang harus dimiliki oleh guru, di antaranya: memiliki kepribadian yang kuat, berwibawa, dan berakhlak mulia, serta menjadi panutan bagi siswa. Penelitian ini diharapkan dapat memberikan kontribusi dalam pengembangan kompetensi kepribadian guru di bidang Pendidikan, serta dapat memberikan sumbangsih terhadap para akademisi, guru dan masyarakat pada umumnya.